The Importance of Non-Conviction Based (NCB) Regulations For Asset Confiscation in Illegal Investment - Asmarani Ramli; Dodik Setiawan Nur Heriyanto; Fezer Tamas; Dian Latifiani (Journal of Law and Legal Reform, 2024)
The purpose of this research is to find out the importance of Non-Conviction Based (NCB) asset confiscation management in illegal investment cases in Indonesia. NCB is a method of confiscating assets that allows the state to confiscation assets without a court order on past criminal convictions. This article argues that controlling the NCB is important to ensure the effectiveness of asset recovery in illegal investment cases and to prevent law enforcement officials from abusing their powers. This research uses a qualitative approach and examines relevant laws and regulations, court decisions and academic writings along with a brief description of the situation in the European Union. The findings in this study indicate that the existing laws and regulations in Indonesia for implementing NCB are inadequate. Hence, asset expropriation in illegal investment cases cannot be carried out without a court order on past criminal decisions. This study recommends making a law on asset confiscation for illegal investment cases that can provide clear criteria and procedures in civil procedural law for the use of the NCB mechanism similar to those exist in a number of EU Member States.